2021
DOI: 10.3390/jcm10214863
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Diabetes Mellitus on the Recurrence of Atrial Fibrillation after Ablation

Abstract: Diabetes mellitus (DM) plays a crucial role in the regulation of atrial fibrillation (AF). This study aimed to evaluate the outcome of pulmonary vein isolation (PVI) using a single-shot device in patients with AF and DM. A total of 531 consecutive patients undergoing initial cryoballoon (CB)-guided PVI were evaluated. Two hundred eighty-one patients (53%) suffered from paroxysmal AF (PAF; mean age 51 ± 23.2 years, 26% female), 250 patients (48%) from persistent AF (PERS; 64 ± 10.0 years old, 30% female) and 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…1,4,5 Several studies point out the importance of LGE CMR imaging for the visualization of individual atrial fibrosis prior to the ablation procedure. [4][5][6][7] In our study, LGE CMR revealed an intermediate amount of 21.41% ± 6.32% of LA fibrosis consistent with Utah stages II-III. Importantly, no PERS AF patient was assigned to Utah stage I as all patients had more than 10% fibrosis of the LA.…”
Section: Lge Cmr Imaging In Pers Afsupporting
confidence: 66%
“…1,4,5 Several studies point out the importance of LGE CMR imaging for the visualization of individual atrial fibrosis prior to the ablation procedure. [4][5][6][7] In our study, LGE CMR revealed an intermediate amount of 21.41% ± 6.32% of LA fibrosis consistent with Utah stages II-III. Importantly, no PERS AF patient was assigned to Utah stage I as all patients had more than 10% fibrosis of the LA.…”
Section: Lge Cmr Imaging In Pers Afsupporting
confidence: 66%
“…Meanwhile, a second CB-system (POLARx, Boston Scientific) became available. First clinical experiences with this novel system reported comparable efficacy and safety, but differences in terms of biophysiological parameters [14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 97%
“…Univariate logistic regression analysis revealed that serum HMGB1post released from the left atrium was associated with AF recurrence (OR: 3.90 [1.16–13.08], p = .03). Next, some common clinical risk factors for AF recurrence were adjusted in a multivariate logistic regression analysis based on previous literature, 19 , 20 , 21 clinical knowledge, and statistically significant covariates in univariate analysis. The risk factors included age, female sex, AF period, CHADS2‐VASc score, hypertension, diabetes mellitus, peripheral arterial diseases, LA diameter, LAVI, LVEF, and HMGB1post.…”
Section: Resultsmentioning
confidence: 99%
“…HMGB1post released from the left atrium was associated with AF recurrence (OR: 3.90 [1.16-13.08], p = .03). Next, some common clinical risk factors for AF recurrence were adjusted in a multivariate logistic regression analysis based on previous literature, [19][20][21] 2).…”
Section: Univariate Logistic Regression Analysis Revealed That Serummentioning
confidence: 99%